Novel Bifunctional Zn–Sn Composite Oxide Catalyst for the Selective Synthesis of Glycerol Carbonate by Carbonylation of Glycerol with Urea. Issue 3 (9th December 2015) - Manjunathan, Pandian; Ravishankar, Raman; Shanbhag, Ganapati V.
Abstract: A novel Zn–Sn composite oxide is reported as a solid bifunctional catalyst for glycerol carbonylation to give glycerol carbonate in high yields. It was prepared by coprecipitation, solid‐state and evaporation methods. Physico‐chemical properties of the catalysts were investigated by XRD, N2 sorption, temperature‐programmed desorption, SEM, and TEM techniques. Coprecipitation was found to be better than the other two methods for carbonylation of glycerol. Higher activity of the catalyst was attributed to a high amount of active sites. A series of Zn–Sn composite oxides with different metal contents and effect of calcination on glycerol carbonate synthesis were also studied. The correlation of activity with total active sites of the catalyst was obtained. Zn–Sn composite catalyst with Zn/Sn molar ratio=2:1 calcined at 600 °C exhibited 96.0 % glycerol conversion with 99.6 % selectivity towards glycerol carbonate under optimized reaction conditions. The catalyst was recycled four times with a marginal decrease in activity. Abstract : Performance promotion : Zinc–tin composite oxide catalysts are prepared by three different methods and evaluated for the synthesis of glycerol carbonate by carbonylation of glycerol with urea. The superior catalytic activity of the catalyst prepared by the coprecipitation method is mainly attributed to the presence of high amounts of acidic and basic sites.